KONTRIBUSI SELF ESTEEM TERHADAP KECANDUAN GAME ONLINE - Rizka Heni (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Being addicted to online game is a kind detrimental behavior that could harm oneself. Such addiction is influenced by various factros, two of which are self esteem. This research aims to describe: (1) self esteem of the students of SMA Pertiwi 1 Padang, (2) students’ addiction to online games at SMA  Pertiwi 1 Padang, (4) the contribution of self esteem toward the students’ addiction to online games, (5) the contribution of self esteem toward the students’ addiction to online games, This research applied quantitative approach and correlational technique. The population of the research was all of students registered in the second semester of Academic Year 2016/2017. By using purposive sampling technique, 243 students were chosen as the samples. The instrument of the research were inventory Self esteem (CFSE-2), the scale of addiction online games (KGO), and the scale self control (SC) by of Likert model. The data obtained were analyzed by using simple and multiple regression technique. The results of the research reveal that,: (1) the students’ self esteem could be categorized as “midle”, (2) the students’ self control and addiction to online games could be classified as “adequate”, (3) the students’ self esteem gives significant contribution (11 %). The implication of the research findings could be regarded as an input for the Guidance and Counseling  teachers  in designing  guidance and counseling program for the the students.